An Analysis of the Factors Contributing to Anxiety in English Language Learning Among College Students - Zakaria Zakaria (Jurnal Pendidikan Indonesia Gemilang, 2025)
Foreign Language Anxiety (FLA) is a common phenomenon among students, particularly those learning a foreign language. This study aims to investigate the factors that cause students to experience anxiety when learning English. The research method employed is descriptive with a qualitative approach. Data were gathered using in-depth interviews, observations, and questionnaires distributed to 100 students from various departments at Universitas Sultan Ageng Tirtayasa. The study's findings revealed that the primary causes of anxiety are (1) fear of making mistakes in front of friends, (2) lack of confidence in English language skills, (3) pressure from lecturers or a competitive learning environment, (4) less interactive teaching methods, and (5) a lack of preparation and basic knowledge of English. Furthermore, students who had negative experiences with previous English language learning exhibited higher levels of anxiety. This study concludes that psychological, pedagogical, and social factors all have a significant impact on student anxiety levels. As a result, efforts must be made to create a supportive learning environment, such as using more inclusive teaching methods, increasing student self-esteem, and providing adequate guidance. This research is expected to help the development of more effective English learning strategies in higher education.